Pengembangan Media Video Pembelajaran Untuk Mengembangkan Kemampuan Berpikir Simbolik Pada Anak Usia 5-6 Tahun - Maria Dissriany Vista Banggur; Adriani Tamo Ina Talu; Shinta Esabella; Rodianto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to develop the symbolic thinking skills of children aged 5-6 years in Santa Clara Ka Redong Kindergarten using learning video media. This type of research is development research using the ADDIE Model. The ADDIE model consists of several components, namely: analysis, design, develop, implementation and evaluation. The results of the study stated that the use of learning video media can help children aged 5-6 years to develop symbolic thinking skills consisting of: children are able to mention symbols of numbers 1-10, children are able to show symbols of numbers 1-10, children are able to mention symbols of numbers 1-10 sequentially, children are able to use number symbols in counting many images, children are able to use number symbols in summing images, Children are able to use number symbols in subtracting images, Children are able to mention the number of images according to the number symbol, Children are able to show the number of images according to the number symbol, Children are able to match the number of images according to the number symbol, Children are able to mention vowels and consonants, Children are able to mention the number of letters of vowels and consonants, Children are able to name objects, Children are able to represent objects in the form of pictures, The child can represent objects in written form